Granuloma annulare: a case-control study of possible associated diseases. - Rosa Fornons-Servent; Andrea Bauer-Alonso; Càudia Llobera-Ris; Rosa María Penín; Joaquim Marcoval (Mattioli1885, 2022)
Introduction: Granuloma annulare (GA) has been reported as associated with multiple diseases, mainly diabetes mellitus (DM), thyroid diseases, and dyslipidemia. However, the high prevalence of some of these illnesses makes it difficult to assess whether the association is real or fortuitous. Our objective was to analyse the clinical features of our GA patients and the possible associations. Methods: This is a retrospective observational study of 225 patients with biopsy-proven GA diagnosed between 2009 and 2019 in a referral university hospital in Barcelona, Spain. Clinical charts were reviewed to obtain clinical data. As a control group we used a random list of 225 patients diagnosed in the hospital's traumatology department in the same period, matched by age and sex. Results: Diabetes was diagnosed in 40 GA patients (18%) (34 in the control group, 15%) and hypothyroidism in 33 (15%) (22 in the control group 9.8%); the differences were not significant. We also did not detect any association with uveitis, sarcoidosis,  necrobiosis lipoidica, Sweet's syndrome, HIV infection, hepatitis B, or haematological malignancies. We only detected a possible association with hepatitis C (6 GA patients, 2.7%, versus 0 controls, p = 0.03), and hypercholesterolemia  (108 GA patients, 48%, versus 79 controls, 35%, p = 0.007). Conclusions: The possible pathogenic explanations for the association with hepatitis C and hypercholesterolemia seem unlikely. We consider that the association of GA with other diseases, including hypercholesterolemia and hepatitis C, is doubtful and that it there is no justification rule out possible associated diseases in patients with GA.